2019
DOI: 10.1177/1521025119882358
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Rita: A Social Cognitive Approach to (First-Generation) Students’ Retention

Abstract: Students who are the first in their family to go to university (first-generation students [FGS]) are still underrepresented at universities. One of the considered reasons for this is their lack of social support. Our study followed a group of German students at two time points: after their first educational choice and at the end of their first semester. According to social cognitive career theory, we tested for the effect of self-efficacy beliefs on intention to drop out, mediated by confidence in vocational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…For instance, a study demonstrated that students who commute and spend less time actively engaged on campus have a more challenging time adjusting to university life compared to students who reside on campus (Mehta et al., 2011). Furthermore, being embedded in a supportive environment has a positive impact on students’ intentions to persist in their studies and reduces the likelihood of dropout (Wittner et al., 2019). However, the emergence of additional levels of effectiveness indicates that there are other significant factors for students at the beginning of their university journey.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study demonstrated that students who commute and spend less time actively engaged on campus have a more challenging time adjusting to university life compared to students who reside on campus (Mehta et al., 2011). Furthermore, being embedded in a supportive environment has a positive impact on students’ intentions to persist in their studies and reduces the likelihood of dropout (Wittner et al., 2019). However, the emergence of additional levels of effectiveness indicates that there are other significant factors for students at the beginning of their university journey.…”
Section: Discussionmentioning
confidence: 99%
“…Even though people make career decisions throughout their lives, such decisions are rarely simple (Patton & Creed, 2001). The choice to study is one of the first professional decisions that people make, but it is also perceived as life-defining (Wittner et al, 2019). Confidence in vocational choice-a similar concept to career decidedness-describes one's level of confidence in one's chosen career and, in the context of students, specifically one's confidence in and commitment to one's chosen course of study (Gordon, 1998;Li et al, 2019;Robbins et al, 2006).…”
Section: Confidence In Vocational Choicementioning
confidence: 99%
“…A developmental network that provides an individual with vocational and socio-emotional support further helps individuals reach career relevant outcomes, such as work satisfaction (Higgins, 2000) and salary (Murphy & Kram, 2010), and it also increases self-efficacy beliefs (Dobrow & Higgins, 2005;Ragins & Kram, 2007) and optimism (Higgins et al, 2010). In higher education, it is an important factor linked to academic achievement , performance (Thiele et al, 2019), and retention (Wittner et al, 2019), as well as academic satisfaction (Wittner & Kauffeld, 2021) and career planning (Wittner & Kauffeld, 2021).…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that FGS and NFGS differ in terms of intergenerational and informational support in particular because of the lack of support with which their parents can provide them (Dennis et al, 2005;Terenzini et al, 1996). A study analysing the effect of career certainty in prospective jobs on students' dropout intentions found a buffering effect of the quality of the support network only for FGS (Wittner et al, 2019). Empirical research shows the importance of social networks, both as a direct antecedent of career-relevant outcomes and indirectly through the perceived support.…”
mentioning
confidence: 99%